Prevalence and Presentation of Thyrotoxicosis at Sialkot (Medical Forum Monthly, 2024)
Objective: To assess the Prevalence and Presentation of Thyrotoxicosis at Sialkot.Study Design: Prospective Study.Place and Duration of Study: This study was conducted at the Idris Teaching Hospital (SMS) Sialkot and Allama Iqbal Memorial Teaching Hospital (KSMC) Sialkot from January 2014 to April 2017.Materials and Methods: We included in this prospective study 100 newly diagnosed patients of. Patients were examined for their signs and symptoms as well as their clinical and family history of thyroid disorders. The blood samples of these patients were drawn and preserved at -80C. Patients were clinically diagnosed into hyperthyroidism by thyroid function test utilizing RIA. Patients having clinically visible enlarged swelling in front of neck were subjected to 99Tc Pertechnetate thyroid imaging. Patients in this study were of all ages and both genders. An informed consent was obtained from each individual participant. The data was recorded on designed performa. Initial screening included complete thyroid profile to identify thyrotoxicosis.Results: In this study the prevalence of the patients of Thyrotoxicosis was higher (31 %) n=31 at the age group of 41-50 years as compared to other age groups. Maximum (90%) n=90 patients were females as compared to male (10%) n=10. The patients of Thyrotoxicosis from rural population were (68%) n=68 & (32%) n=32 from urban population. Loose stools were present in (49%) n=49, (7%) in male and (42%) in female, anxiety was present in (85%)n=85 patients (10%) in male & (75%) in female, hair loss was present in (35%) n=35 patients ,(05%) male & (30%) in female. Menstrual irregularities was present in (45%) n=45 of the female, heat intolerance was present in (64%) n=64 of the patients (4%) in male & (60%) in female, periorbital edema was present in (24%) n=24 of the patients, (01%) in male and (23%) in female, hoarseness was present in (38%) n=38 of the patients, (03%) in male and (35%) in female, sweating was present in (68%) n=68 of the patients, (05%) male & (63%) in female, exophthalmos was present in (49%) n=49 of the patients, (06%) in male & ( 43%) in female, tremors were present in (74%) n=74 of the patients, (10%) in male & ( 64%) in female, shortness of breath was present in (70%) n=70 of the patients, (05%) in male & (65%) in female, increased appetite was present in (53%) of the patients, (06%) in male & (47%) in female, polyuria was present in (40%)n=40 of the patients, (04%) in male & (36%) in female, goiter was present in (75%) n=75 of the patients, (09%) of male & (66%) in female of the Thyrotoxicosis. The mean age was 40±13SD. The mean ±SD of BMI was 23.65±3.70, 19.66±3.78 in male & 25.67±4.70 in female, free T3 was 7.25±1.9nmol/l as total 7.3±1.8 nmol/l in male & 6.85±2.4 nmol/l in female, total TSH(uU/ml) was 0.63±0.17(uU/ml), 0.63±0.15(uU/ml) in male & 0.59±0.29(uU/ml) in female.Conclusion: People awareness about the dietary iodine intake is necessary in our country to overcome the increased prevalence of the thyroidal dysfunction in our population. It is observed that hyperthyroid state is more common in our population.